RESISTÊNCIA A PENETRÇÃO DO SOLO SOB DIFERENTES TIPOS DE COBERTURA VEGETAL. - TENÓRIO NETO, Joaquim; MARTINS, Murilo Battistuzzi; FAGUNDES, Ruan Camilo; JÚNNYOR, Wellingthon da Silva Guimarães; SILVA, Fagner Luiz Rodrigues (ANAIS DO ENIC, 2024)
-